International economic law and domestic law: case study to the Chilean Anti-competitive market distortions Office - Sánchez González, Ignacio Antonio (Latin American Journal of Trade Policy, 2021)
This article provides a legal analysis of the Chilean Anti-Competitive Market Distortions Office (or “Comisión Antidistorsiones”). This office was established by Law No. 18,525 of 1986, and, after several legal amendments, complies with the international obligations that Chile has undertaken in the Marrakech Agreement of 1994 and four of its annexes, with respect to practices that may have negative effects on international trade, and ultimately, damage to local production and consumers. To this end, the theoretical bases are established on the relationship between International Law and domestic law, with special attention to this specific field of the international legal system, International Economic Law. Then, the multilateral trade system and the rules derived from the World Trade Organization are briefly discussed to contextualize the investigated topic. Finally, we proceed to analyze the composition, effectiveness, and consequences of the Office’s decisions, considering the relevant administrative and procedural rules and their contestation processes, in order to determine the level of compliance that Chile gives to the international rules in this matter.